Hidden diversity inside bromeliads: a new species of Cavichiana from Espírito Santo, southeastern Brazil (Insecta: Hemiptera: Cicadellidae: Cicadellini) - Timóteo, Ágatha; Quintas, Victor; Alves, André Almeida; Mejdalani, Gabriel (Zootaxa, 2026)
The sharpshooter genus Cavichiana Mejdalani et al., 2014 previously included three species: C. bromelicola Mejdalani et al., 2014 (type species), C. alpina Quintas et al., 2020, and C. caelivittata Mejdalani et al., 2023. These species occur exclusively on bromeliads in southeastern and southern Brazil. Here we describe a new species, C. coeruleomaculata, from Caparaó National Park, municipality of Ibitirama, state of Espírito Santo, southeastern Brazil (so far, the northernmost known record of the genus). The new taxon can be distinguished by the head with small bluish-white spots; forewings with large bluish-white transcommissural macula with anterior part covering scutellum; and aedeagus with conspicuous posterior projection directed dorsally and lacking apical crown of spines. An updated diagnosis of Cavichiana is presented, considering character variation found in species described after the original genus description. Also, a key to the known species of Cavichiana is provided and the distribution of the genus is discussed.